Practice Variation in Antenatal Steroid Administration for Anticipated Late Preterm Birth: A Physician Survey - Battarbee, Ashley N.; Clapp, Mark A.; Boggess, Kim A.; Kaimal, Anjali; Snead, Carrie; Schulkin, Jay; Aliaga, Sofia (American Journal of Perinatology, 2019)
Objective The objective of this study was to measure knowledge and practice variation in late preterm steroid use.Study Design Electronic survey of American College of Obstetricians and Gynecologists (ACOG) members about data supporting the ACOG/Society for Maternal-Fetal Medicine (SMFM) recommendations and practice when caring for women with anticipated late preterm birth (PTB), 340/7 to 366/7 weeks.Results Of 352 administered surveys, we obtained 193 completed responses (55%); 82.5% were generalist obstetrician-gynecologists (OB/GYNs), and 42% cared for women with anticipated late PTB at least weekly. Most believed that late preterm steroids provided benefit by reducing respiratory distress syndrome (93%), transient tachypnea of the newborn (83%), and neonatal intensive care unit admission (82%). More than half administered late preterm steroids to women with multiple gestations (73%), and pregestational diabetes (55–80%) depending on glycemic control. OB/GYNs administered steroids to insulin-dependent and poorly controlled diabetics more often than MFMs (75 vs. 46% and 59 vs. 37% respectively, p < 0.05 for both). While providers believed there was increased maternal hyperglycemia (88%) and neonatal hypoglycemia (59%), 88% believed neonatal respiratory benefits outweighed these risks. Respondents agreed research is needed to determine who are appropriate candidates (77%) and how to minimize adverse outcomes (82%).Conclusion Most providers are administering late preterm steroids to all women, even those populations who have been excluded from previous trials. Despite widespread use, providers believe more research is needed to optimize management.
Keywords: survey; late preterm; antenatal corticosteroids